DISTRIBUTION OF MARINE CLADOCERANS IN THE NORTHERN BERING SEA AND THE CHUKCHI SEA (17th Symposium on Polar Biology) - オンベ, タカシ; タニムラ, アツシ; フクチ, ミツオ; ハットリ, ヒロシ; ササキ, ヒロシ; マツダ, オサム; ONBE, Takashi; TANIMURA, Atsushi; FUKUCHI, Mitsuo; HATTORI, Hiroshi; SASAKI, Hiroshi; MATSUDA, Osamu (National Institute of Polar Research, 1996)
P(論文) Distribution and abundance of marine cladocerans were studied in the northern Bering Sea and the Chukchi Sea during the period from July to October in 1988-1990. Two species of marine onychopod cladocerans belonging to Podonidae, Evadne nordmanni LOVEN and Podon leuckarti G. O. SARS, were detected in both seas at varying densities during this period. In particular, at stations located in eastern Bering Strait, maximum densities of 912 indiv・m^<-3> for E. nordmanni and 1725 indiv・m^<-3> for P. leuckarti were recorded in July 1989. In addition, a few specimens of the marine ctenopod species belonging to Sididae, Penilia avirostris DANA, and a single specimen of the freshwater anomopod species belonging to Moinidae, Moina sp., were collected at the easternmost nearshore station in Bering Strait only once, in July 1989. This appears to be the northernmost record for P. avirostris. Abundances of cladocerans were higher in July-August than in September-October, all species preferring less saline, chlorophyll-rich, warmer waters than colder waters of higher salinity. In both podonid species, gamogenetic individuals were found together with more prevalent parthenogenetic females. Proportions of gamogenetic individuals were less pronounced in July-August, but increased in September and October, sometimes surpassing 86% of the whole population, beyond the proportion recorded in mid-latitudinal populations in the Atlantic and the Pacific waters. The resting egg production is considered as an effective life-history strategy for the maintenance and survival of populations of E. nordmanni and P. leuckarti in these boreal and polar seas. departmental bulletin paper